ANALISA KEBUTUHAN MODAL KERJA DALAM PENENTUAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE VARIABEL COSTING DAN ACTIVITY BASED COSTING SERTA MANFAATNYA UNTUK PERTUMBUHAN LABA USAHA (STUDI KASUS PADA UKM TAHU BOGA RASA PERIODE JANUARI – DES - Ihsan Nasihin (Program Studi Akuntansi, 2019)
This research is a descriptive research with quantitative approach done on UKM Tahu Boga Rasa. This study has four main objectives. First, aims to find out the analysis of working capital needs in determination the cost of production by using the method of variable costing and activity based costing. Second, to know the analysis of working capital needs for profit growth. Thirdly, to determine of cost of production by using variable costing and activity based costing method for profit growth. Fourth, to analyse of working capital needs in determine the cost of production by using the method of variable costing and activity based costing and its benefits for profit growth. The need for working capital in determine the cost of production by using the variable costing method is lower than the determination of cost of production method of activity based costing and its benefits for profit growth is to show the same value of profit growth, this is caused by the components of cost of production by using costing and activity based costing variables are different, so the value of working capital needs based on the determination of cost of production by using the method of variable costing is lower than the determination of cost of production using activity based costing method. In addition, the relatively fixed selling price results in relatively equal net profit value, but the production cost occurrs fluctuations and daily life expenses of the owner of UKM Tahu Boga Rasa is still borne by the business or not separated. Keywords: Working Capital Needs (KMK), Cost of Production of Variable Costing, Cost of Production Activity Based Costing, Profit Growth